2017
DOI: 10.1111/jasp.12489
|View full text |Cite
|
Sign up to set email alerts
|

Comparing educational interventions: Correcting misperceived norms improves college students' mental health attitudes

Abstract: This research targeted potential psychological contributors to college students' low levels of helpseeking for mental distress using a field experiment. Researchers randomly assigned 520 undergraduates to 15-min interventions: a novel, theory-driven social norms intervention correcting misperceived distress, stigma, and help-seeking norms; a general education intervention increasing mental health awareness; and a stress management active control condition. The norms intervention instilled more accurate percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…It follows the tradition of educational intervention research (cf. Hunt and Hunt, 2004; Mansoori-Rostam and Tate, 2017; Shiina et al, 2017; Turetsky and Sanderson, 2017). One focus of the study is on the coverage and analysis of the participants’ complex ICT biography (family/school) in connection to gender stereotypes and the participants’ interest in ICT professions.…”
Section: Methodsmentioning
confidence: 99%
“…It follows the tradition of educational intervention research (cf. Hunt and Hunt, 2004; Mansoori-Rostam and Tate, 2017; Shiina et al, 2017; Turetsky and Sanderson, 2017). One focus of the study is on the coverage and analysis of the participants’ complex ICT biography (family/school) in connection to gender stereotypes and the participants’ interest in ICT professions.…”
Section: Methodsmentioning
confidence: 99%
“…Due to lack of enough education and experiences of medical camps the reason may be that they do not know about mental treatment. A study conducted in college students found that they improve help seeking towards mental illness in general education [33].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are compelling, but these and similar interventions (e.g., Turetsky & Sanderson, 2018) have capitalized on pre‐existing social connections by having peers—fellow university students—deliver the intervention. This would suggest that policymakers stand to gain more by encouraging these discussions within communities and social networks than by transmitting this information themselves.…”
Section: Psychological Processesmentioning
confidence: 99%